2004
DOI: 10.1037/0033-2909.130.4.601
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress and the Human Immune System: A Meta-Analytic Study of 30 Years of Inquiry.

Abstract: The present report meta-analyzes more than 300 empirical articles describing a relationship between psychological stress and parameters of the immune system in human participants. Acute stressors (lasting minutes) were associated with potentially adaptive upregulation of some parameters of natural immunity and downregulation of some functions of specific immunity. Brief naturalistic stressors (such as exams) tended to suppress cellular immunity while preserving humoral immunity. Chronic stressors were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
1,908
15
65

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,649 publications
(2,037 citation statements)
references
References 373 publications
(239 reference statements)
49
1,908
15
65
Order By: Relevance
“…Further, given that stress, social support, and self-esteem are important psychological mediators of unemployment stress, health and endocrine function (Segerstrom and Miller 2004, Pruessner et al 2005, Uchino 2006, O'Donnell et al 2008 we also wanted to confirm that our unemployed group were highly stressed and also tested whether they were associated with cortisol and DHEAS responses in these groups.…”
Section: Egerstro a D O Co Ormentioning
confidence: 99%
“…Further, given that stress, social support, and self-esteem are important psychological mediators of unemployment stress, health and endocrine function (Segerstrom and Miller 2004, Pruessner et al 2005, Uchino 2006, O'Donnell et al 2008 we also wanted to confirm that our unemployed group were highly stressed and also tested whether they were associated with cortisol and DHEAS responses in these groups.…”
Section: Egerstro a D O Co Ormentioning
confidence: 99%
“…For example, a recent meta-analysis concluded that the number of stressful life events an individual experienced was associated with a decrease in some immune status markers, including natural killer cells and a marginal reduction of T-cytotoxic lymphocytes [55]. Although the specific mechanisms linking stress and immune functioning in HIV-infected patients are not fully understood, these findings have stimulated interest in the possibility that stress management interventions may impact disease progression.…”
Section: Health Status Markersmentioning
confidence: 99%
“…For example, acute stress can enhance the acquisition and expression of immunoprotection by activation of bodily defences prior to wounding or infection One primary mechanism by which acute psychological stress induces immune response is through rapid changes in leukocyte distributions in the peripheral circulation (Bosch et al, 2008). Studies investigating acute short-term stressors in humans, such as public speaking, have reported brief increases of natural killer (NK) cell numbers and other leukocyte subtype cell numbers, a reduction in lymphocyte proliferation, an increase in pro-inflammatory cytokine production, and reduced healing capacity of the skin (Altemus et al, 2001; Segerstrom and Miller, 2004). Studies of acute (psychological) stress due to physical danger have used first-time tandem skydive (Schedlowski et al, 1993), as this challenge has the advantage of representing real risk, eliciting reliable effects, and yet permitting a high degree of experimental control.…”
Section: Introductionmentioning
confidence: 99%